GA3 priming, biopriming and hydropriming effect on quality nursery production of China aster (Current Horticulture, 2024)
The study was carried out at Dr YS Parmar University of Horticulture and Forestry, Nauni, Solan, on China aster [Callistephus  chinensis (L.) Nees] cv ‘Poornima’ and ‘Kamini’ in nursery under open field conditions in randomized block design (factorial)  comprising eight seed priming treatments viz control, hydropriming with water, priming with GA3 (50, 100 and 150 ppm)  and biopriming with Trichoderma viride @ 1× 104 cfu/ml, 1× 105 cfu/ml and 1× 106 cfu/ml for 24 hr. There was maximum speed  of germination (18.97, 21.58), germination percentage (83.17, 86.33 %), root length (2.87, 2.93 cm), shoot length (6.39, 6.59 cm),  seedling length (9.26, 9.52 cm), seedling dry weight (227.67, 248.30 mg), seed vigour index-I (769.89, 822.19), seed vigour index II (18,934.33, 21,436.62); minimum time taken to seed germination (12.72, 11.33 days) and days required to reach 4-6 leaf stage  (23.70, 22.33 days) with priming treatment GA3 (100 ppm) in Poornima and Kamini, respectively. Hence, it is concluded that  seeds of Kamini treated with GA3 (100 ppm) for 24 hr obtained best results for most of the desirable character for quality nursery  production of China aster.
Keywords: Kamini; Nursery; Poornima; Priming; Quality